Nilai Ekonomi Sumberdaya Ikan Delah (Caesio Teres) di Desa Kelong Kabupaten Bintan Kepulauan Riau - Fahrizal, Uray; Khairunnisa, Khairunnisa; Hafsar, Khairul (MarIslands, 2021)
One of the catches of fishermen from Kelong Village is Delah Fish (Caesio teres) one of the target fish species that have high economic value and this fish also meets the demand of the export market, delah fish has a fairly high market and export price, the purpose of research is to examine the economic value of fish. Delah (Caesio teres) to know the role of Delah Fish (Caesio teres) in absorbing labor and the contribution of Delah Fish (Caesio teres) to the income of fishermen's families in Kelong Village. This research was carried out from March to April 2021. This study used a survey method with primary data collection using direct fisherman interviews and secondary data consisting of documents. Determination of respondents is done by the census method, namely fishing fishermen who use longline fishing gear, and traps totaling 32 respondents, the census method is a method that takes one population group as a whole sample. The tools of this research are, a questionnaire, writing style, and calculator. The procedure of this research includes 2 procedures, namely preparation and implementation. The preparation stage consists of 3 activities, (1) survey of research sites, (2) research permit at the village office, (3) conducting interviews with village office informants, and (4) making research question guides (questionnaires). The results of this study obtained the economic value of delah fish resources in Kelong Village, the total economic value was Rp. 2,879,724,000/year, labor absorption of delah fish resources in Kelong Village was 41 people or 7.96%, the contribution to the average income fish fishermen, the income of delah fish fishermen is Rp. 16,500,000/year or 70%. Family members of delah fish fishermen who work are Rp. 7,068,750/year or 30%.